Kajian Disrupsi Pada Transportasi Umum (Angkot) Di Kecamatan Nanggalo,Kota Padang Dengan Metode Importance Performance Analisis - Prawira, Dazaqki; Roza, Angelalia; Wahab, Wilton; JF, Anggun Pratiwi (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2025)
This study aims to analyze the impact of disruption caused by the development of online transportation on public minivans (angkot) in the Nanggalo District, Padang City, and to assess changes in public interest in choosing urban transportation modes. Disruption refers to innovation that replaces existing systems with new methods, and this phenomenon is also occurring in spatial planning in Indonesia, particularly in the transportation sector. In recent years, angkot, as a primary mode of transportation, has experienced a decline in passenger numbers and fleet size due to the emergence of online transportation applications such as Gojek and Grab. The methodology employed in this research is Importance Performance Analysis (IPA). The findings indicate that 73% of respondents prefer using online transportation, leading to a 48.67% decrease in angkot passengers. The average frequency of angkot operating during peak hours is recorded at only 3 vehicles per hour for the Pasar Nanggalo – Lapai route and 5 vehicles per hour for the Pasar Nanggalo – Gunung Pangilun route. Furthermore, the load factor for the Pasar Nanggalo – Lapai route is 41.67%, while for the Pasar Nanggalo – Gunung Pangilun route, it is 48.61%. The average waiting time for angkot on the Pasar Nanggalo – Lapai route is 13 minutes, whereas for the Pasar Nanggalo – Gunung Pangilun route, it is 7 minutes. This study recommends enhancing the quality of angkot services, including more regular scheduling, improved cleanliness, and increased comfort during trips. Additionally, it is crucial for local governments to formulate policies that support the sustainability of angkot through driver training programs and innovations in public transportation systems. By doing so, it is expected that angkot can adapt to technological advancements and meet the evolving needs of the community.